Biallelic disruption of PKDCC is associated with a skeletal disorder characterised by rhizomelic shortening of extremities and dysmorphic features. Issue 12 (26th November 2018) - Sajan, Samin A; Ganesh, Jaya; Shinde, Deepali N; Powis, Zöe; Scarano, Maria I; Stone, Jennifer; Winter, Susan; Tang, Sha
Abstract : Background: During mouse embryonic development the protein kinase domain containing, cytoplasmic ( Pkdcc ) gene, also known as Vlk, is expressed in several tissues including the ventral midbrain, with particularly strong expression in branchial arches and limb buds. Homozygous Pkdcc knockout mice have dysmorphic features and shortened long bones as the most obvious morphological abnormalities. The human PKDCC gene has currently not been associated with any disorders. Objective: To use clinical diagnostic exome sequencing (DES) for providing genetic diagnoses to two apparently unrelated patients with similar skeletal abnormalities comprising rhizomelic shortening of limbs and dysmorphic features. Methods: Patient–parents trio DES was carried out and the identified candidate variants were confirmed by Sanger sequencing. Results: Each patient had a homozygous gene disrupting variant in PKDCC considered to explain the skeletal phenotypes shared by both. The first patient was homozygous for the nonsense variant p.(Tyr217*) (NM_1 38 370 c.651C>A) expected to result in nonsense-mediated decay of the mutant transcripts, whereas the second patient was homozygous for the splice donor variant c.639+1G>T predicted to abolish the donor splice site by three in silico splice prediction algorithms. Conclusions: Biallelic gene disrupting variants in PKDCC in humans, just like in mice, cause dysmorphic features and rhizomelic shortening of limbs.